The promises and properties of rapidly growing companies : gazelles - Becker-Ritterspach, Florian A. A., 1972-; Dörrenbächer, Christoph, 1961-; Tomenendal, Matthias (Emerald Publishing Limited, 2022)
The Promises and Properties of Rapidly Growing Companies contributes to contemporary thought on so-called gazelles - high performing market players that create many jobs and promise strong welfare effects. Moving away from the well-established idea of firm growth as a continuous process, the contributions of this edited volume add to the growing body of innovative gazelle related research in three ways: Firstly, systematically taking stock of the international gazelle growth literature and proposing a theoretical growth model, which supports the rare and temporal nature of gazelle growth. Secondly, empirically investigating German gazelles and the German gazelle policy stance, counterbalancing the current Anglo-American research bias. Thirdly, addressing lesser studied or omitted gazelle-related themes such as gazelles' internationalization, the dark sides of gazelles' growth, and gazelles' corporate citizenship. The Promises and Properties of Rapidly Growing Companies is a valuable resource for academics, managers, policy makers and civil society actors concerned with firm growth, economic development and the corporate social responsibility of rapidly growing firms.
Keywords: Business enterprises.; Economic development.; Business & Economics -- Development -- Business Development.; Business innovation.; elektronické knihy; electronic books